(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
Central Nervous System (CNS) tumor comprises about 2-5% of all tumors. Quite a large number of patients with CNS tumor undergo surgical treatment in Bangladesh. Surgical treatment is greatly facilitated by the use of intraoperative diagnosis. The techniques for intraoperative diagnosis of neurosurgical biopsy specimen are frozen section & crush smear cytology. In our study, a total of 64 cases of CNS tumor was evaluated by crush smear. Among them, 54 (84.38%) cases were brain tumor & 10 (15.62%) cases were spinal tumor, with a slight male predominance (M:F = 1.2:1). The mean age of the patients was 31 years. Cerebrum was the commonest site of brain tumor & astrocytoma was the commonest malignant tumor. Among 64 cases, 61 cases were correctly diagnosed by crush cytologic technique. The accuracy of intraoperative cytologic diagnosis was determined in comparison to histologic diagnosis was 95.3%. It is concluded that crush cytologic technique may be considered as a reliable primary diagnostic tool for intraoperative evaluation of CNS tumor. JCMCTA 2015 ; 26 (2) : 40 - 43